Preparation method of double-metal hydroxide functionalized double-layer mesoporous composite adsorbent and application thereof in defluorination

CN118892815BActive Publication Date: 2026-10-13JIANGSU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411316528.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2026-10-13
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

[0004]为了解决现有技术中纳米金属氧化物吸附剂不易收集、动态分离时易引起较大的柱压等问题,同时实现酸性条件下高效除氟,本发明建立了一种双层介孔中空材料负载双金属氢氧化物复合吸附剂的制备方法

Benefits of technology

本发明通过将具有介孔中空结构的高比表面积碳球与双金属氢氧化物结合,双金属锆和镧氢氧化物生长在碳球内外层,丰富的吸附位点可进行高效除氟,在酸性环境中显示出较好的除氟效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118892815B_ABST
    Figure CN118892815B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of adsorption separation functional materials, and discloses a preparation method of a bimetallic oxide functionalized double-layer mesoporous composite adsorbent and a fluorine removal application. The application combines the different hydrolysis rates of phenolic resin and tetraethyl orthosilicate under alkaline conditions to synthesize carbon spheres with double-layer mesoporous hollow structures under the condition of no surfactant assistance. Then, lysozyme is fixed in the carbon spheres through physical adsorption, and the abundant and uniformly distributed groups on the surface of the lysozyme provide conditions for the functional modification of bimetallic hydroxide. The metal salt solution is mixed with the enzyme-loaded carbon spheres at room temperature, and then sodium hydroxide is added to generate zirconium and lanthanum bimetallic hydroxide in situ under alkaline conditions, so that the double-layer mesoporous bimetallic oxide carbon spheres are obtained. The application combines the carbon spheres with double-layer mesoporous hollow structures with bimetallic oxides to achieve excellent fluorine removal performance under acidic conditions, to achieve adsorption equilibrium in 30 min, and the adsorption capacity is 110mg·g ‑1 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of adsorption and separation functional material preparation technology, and relates to the preparation of metal hydroxide adsorbents, especially to a method for preparing a bimetallic hydroxide composite adsorbent grown from a bilayer mesoporous material, and the efficient defluorination application of the adsorbent. Background Technology

[0002] Fluorine (F) is one of the trace elements needed by the human body, mainly found in teeth and bones. Appropriate fluoride intake can prevent tooth decay and promote bone development; however, long-term intake of high concentrations of fluoride can lead to various diseases such as dental fluorosis and skeletal fluorosis. With the rapid development of industries such as new energy batteries, photovoltaics, and phosphate fertilizers, the probability of groundwater pollution by fluoride is constantly increasing. Studies have shown that one-third of the fluoride pollution in my country's rivers and 60% of groundwater is mainly caused by industrial wastewater discharge. Fluorine discharged into the environment without proper treatment can cause local drinking water to exceed fluoride standards, threatening human health. Therefore, exploring efficient fluoride removal methods to meet emission standards is of great significance. Among these methods, adsorption is widely used due to its advantages of simple operation, low cost, and wide availability of materials. Currently available defluorination adsorbents include metal oxides, biomass-based materials, and carbon-based materials. Carbon-based materials have advantages such as large specific surface area and multi-mesoporous structure, but their adsorption capacity for fluoride ions is relatively weak. Metal hydroxides, due to their strong alkalinity and electronic potential, can form stable metal-ligand interactions with fluorides and have a strong affinity for fluoride ions. However, metal hydroxides are easily leached during adsorption and exhibit significant resistance due to the pressure drop in the fixed bed column.

[0003] To achieve efficient fluoride removal under acidic conditions and address the aforementioned problems, metal hydroxides can be loaded onto porous carbon materials. However, how to grow metal hydroxides on mesoporous carbon spheres lacking abundant functional groups is a new challenge that needs to be solved. Lysozyme, with its wide availability, chemical stability, and certain antibacterial properties, serves as a bridge between metal hydroxides and bilayer mesoporous hollow carbon spheres. Bilayer mesoporous carbon spheres with high specific surface area and a mesoporous structure immobilize lysozyme on the carbon spheres through physical adsorption. The abundant functional groups on the surface of lysozyme provide a beneficial platform for the chelation of zirconium and lanthanum ions, generating bimetallic hydroxides in situ under alkaline conditions. Zirconium and lanthanum bimetallic hydroxides exhibit excellent fluoride removal performance under acidic conditions. The prepared bimetallic hydroxide carbon spheres still possess a large specific surface area, and adsorption sites are distributed in both the inner and outer layers of the carbon spheres, laying the foundation for efficient fluoride removal. Currently, no relevant reports have been found. Summary of the Invention

[0004] To address the challenges of collecting nano-metal oxide adsorbents and the resulting high column pressure during dynamic separation in existing technologies, and to achieve efficient fluoride removal under acidic conditions, this invention establishes a method for preparing a bilayer mesoporous hollow material-supported bimetallic hydroxide composite adsorbent. First, hollow carbon spheres (MHCS) with a bilayer mesoporous structure were prepared. Then, enzyme-inotropic carbon spheres (enzyme-MHCS) were prepared by physically immobilizing lysozyme. Zirconium and lanthanum metal ion solutions were mixed with the enzyme-inotropic carbon spheres, and under alkaline conditions, metal hydroxides were generated in situ to prepare a bimetallic hydroxide-functionalized bilayer mesoporous composite adsorbent (Zr-La-MHCS). The application of this adsorbent in fluoride removal was then investigated.

[0005] A method for preparing a bimetallic hydroxide functionalized bilayer mesoporous composite adsorbent includes the following steps: (1) Preparation of double-layer mesoporous hollow carbon spheres (MHCS) Tetraethyl orthosilicate (TEOS), resorcinol, and formalin were added to a solution composed of ammonia solution, deionized water, and ethanol. The mixture was stirred vigorously at room temperature for t1, then TEOS was added and stirring continued for t2. Finally, the mixture was placed in a high-pressure autoclave lined with polytetrafluoroethylene for further hydrothermal treatment. The solid product was collected by centrifugation and dried overnight. After carbonization under N2 atmosphere and removal of the silica template by hydrofluoric acid etching, MHCS nanoparticles were obtained.

[0006] (2) Preparation of enzyme-MHCS Lysozyme LYM was added to deionized water to prepare a lysozyme solution. The MHCS nanoparticles prepared in step (1) were added to the lysozyme solution. LYM was fixed on the MHCS nanoparticles by physical adsorption. The mixed solution was then placed in a centrifuge tube, placed on a shaker for adsorption and fixation, centrifuged, washed with deionized water, and freeze-dried for later use to obtain enzyme-MHCS carbon spheres.

[0007] (3) Preparation of bimetallic oxide functionalized bilayer mesoporous composite adsorbent (Zr-La-MHCS) Lanthanum chloride (LaCl3), zirconium oxychloride octahydrate (ZrOCl2·8H2O), and enzyme-MHCS carbon spheres were dispersed in HCl solution and stirred with a magnetic stirrer for a period of time to allow the metal ions to chelate with the enzyme. Then, NaOH solution was added, and the reaction was continued with stirring. After centrifugation, the mixture was washed with deionized water and freeze-dried to obtain the bimetallic hydroxide functionalized bilayer mesoporous composite adsorbent Zr-La-MHCS.

[0008] In the preferred embodiment of this invention, the bilayer mesoporous hollow carbon nanoparticles (MHCS) in step (1) are synthesized according to existing technology (Self-Organized Mesostructured Hollow Carbon Nanoparticles via a Surfactant-Free Sequential Heterogeneous Nucleation Pathway Hongwei Zhang, Meihua Yu, Hao Song, Owen Noonan, Jun Zhang, Yannan Yang, Liang Zhou, and Chengzhong Yu Chemistry of Materials 2015 27 (18), 6297-6304 DOI: 10.1021 / acs.chemmater.5b01993). The synthesis method used in this invention is disclosed herein: In step (1), the ratio of the initially added tetraethyl orthosilicate (TEOS), resorcinol, formalin, ammonia solution, deionized water, ethanol, and subsequently added TEOS is 2.8 mL: 0.4 g: 0.56 mL: 3.0 mL: 10 mL: 70 mL: 1.5 mL; wherein the concentration of formalin is 37 wt% and the concentration of ammonia solution is 28 wt%. The stirring time t1 is 6 hours, and the stirring time t2 is 24 hours; The hydrothermal treatment was carried out at a temperature of 100℃ for 24 hours. The carbonization temperature is 700℃, and the concentration of hydrofluoric acid is 5%.

[0009] In step (2), the ratio of lysozyme to deionized water is 30-60 mg: 30-50 mL.

[0010] Preferably, the ratio of LYM to deionized water is 30 mg: 40 mL.

[0011] In step (2), the mass-to-volume ratio of MHCS and lysozyme aqueous solution is 30-60 mg: 30-50 mL.

[0012] Preferably, the mass-to-volume ratio of MHCS and lysozyme aqueous solution is 20.0 mg: 40 mL.

[0013] In step (2), the adsorption fixation time is 12.0 h.

[0014] In step (3), the mass-to-volume ratio of LaCl3, ZrOCl2·8H2O, enzyme-MHCS and HCl solution is 20-50 mg: 20-50 mg: 20-50 mg: 20-50 mL.

[0015] Preferably, the mass-to-volume ratio of LaCl3, ZrOCl2·8H2O, enzyme-MHCS, and HCl solution is 25 mg:25 mg:50 mg:30 mL, wherein the concentration of the HCl solution is 0.1 M.

[0016] In step (3), the volume ratio of NaOH solution to HCl solution is 10~20 mL: 20~50 mL, and the concentration of NaOH solution is 1M.

[0017] In step (3), the stirring reaction time is 2.5 h, and the condition is room temperature.

[0018] The bimetallic oxide functionalized bilayer mesoporous composite adsorbent prepared in this invention was used for the deep adsorption and separation of fluoride ions. In an environment of 25°C, 2.0 mg of the prepared adsorbent (Zr-La-MHCS) was placed in 9.0 mL of 50 mg / L fluoride ion solution for adsorption. After 3.0 h, the solution was taken out and the concentration of the adsorbed solution was tested.

[0019] Adsorption capacity calculation formula:

[0020] in C 0 (mg L) -1 )and C e (mg / L) represent the initial and equilibrium concentrations of fluoride ions, respectively. V (mL) is the volume of the test solution. m (g) represents the mass of the adsorbent.

[0021] The adsorption performance of this invention was evaluated according to the following method: Adsorption experiment: 2.0 mg of the adsorbent (Zr-La-MHCS) prepared according to the method described in this invention was added to 9.0 mL of test solution with an initial pH of 2-8 (concentration of 50 mg / L). -1 In the adsorption process, the content of residual fluoride ions after adsorption was determined by ion chromatography, and the adsorption capacity was calculated based on the results. After saturation adsorption, the adsorption effect of Zr-La-MHCS was studied by the adsorption capacity at different concentrations and temperatures. Kinetic adsorption was carried out using different adsorbents under the same conditions. The adsorption effect of Zr-La-MHCS in the presence of competing ions was studied by changing the concentration of impurity ions.

[0022] The beneficial effects of this invention are as follows: This invention combines high specific surface area carbon spheres with mesoporous hollow structures with bimetallic hydroxides. Bimetallic zirconium and lanthanum hydroxides are grown on the inner and outer layers of the carbon spheres, providing abundant adsorption sites for efficient fluoride removal, and exhibiting good fluoride removal performance in acidic environments. Attached Figure Description

[0023] Figure 1 SEM and TEM images of MHCS (a, e), enzyme-MHCS (b, f), and Zr-La-MHCS (c, g) prepared in Example 1; Figure 2 BET diagrams of the original carbon spheres MHCS and enzyme-mediated carbon spheres enzyme-MHCS; Figure 3 The effect of different pH conditions on the adsorption capacity of Zr-La-MHCS and fluoride ions and the corresponding zeta potential; Figure 4 Adsorption kinetics and model fitting curves for different adsorption materials; Figure 5 The adsorption isotherm and model fitting curves for Zr-La-MHCS; Figure 6 This is a comparison diagram of Zr-La-MHCS adsorption and defluorination in the presence of competing ions. Detailed Implementation

[0024] The present invention will be described in detail below with reference to embodiments, so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.

[0025] Example 1

[0026] (1) Preparation of MHCS particles with a size of 200 nm by polymerization Tetraethyl orthosilicate (TEOS, 2.8 mL), resorcinol (0.4 g), and formalin (37 wt%, 0.56 mL) were added to a solution consisting of ammonia solution (3.0 mL, 28 wt%), deionized water (10 mL), and ethanol (70 mL). The mixture was stirred vigorously at room temperature for 6 hours, followed by the addition of 1.5 mL of TEOS and stirring for another 24 hours. The mixture was then further hydrothermally treated at 100 °C in a polytetrafluoroethylene-lined autoclave for 24 hours. The solid product was collected by centrifugation and dried overnight at 50 °C. MHCS was obtained after carbonization at 700 °C under a N2 atmosphere and etching to remove the silica template with hydrofluoric acid (HF, 5%).

[0027] Figure 1a and e are SEM and TEM images of MHCS particles. As can be seen from the images, the particles are uniformly distributed and of uniform size, proving the successful preparation of bilayer mesoporous hollow carbon spheres.

[0028] (2) Preparation of enzyme-MHCS 30 mg of lysozyme (LYM) was added to 50 mL of deionized water to prepare a solution. 50 mg of MHCS nanoparticles prepared in step (1) were added to the lysozyme solution, and LYM was immobilized on the MHCS nanoparticles through physical adsorption. The prepared solution was placed in a centrifuge tube and placed on a shaker for adsorption and fixation for 12 h. After centrifugation, the solution was washed with deionized water and freeze-dried for later use. Enzyme-MHCS was obtained.

[0029] Figure 1 b and f are SEM and TEM images of the lysozyme-inoculated carbon spheres. As can be seen from the images, the carbon sphere shell is thickened and the surface becomes rough, which proves that the lysozyme was successfully immobilized.

[0030] Figure 2 The BET characterization diagrams of MHCS and enzyme-MHCS are shown, proving that their structures are mesoporous.

[0031] (3) Preparation of Zr-La-MHCS 25 mg of lanthanum chloride (LaCl3), 25 mg of zirconium oxychloride octahydrate (ZrOCl2·8H2O), and 30 mg of the enzyme-inactivating carbon spheres prepared in step two were dispersed in 30 mL of HCl (0.1 M) solution. The mixture was stirred magnetically at room temperature for 2.5 h to allow the metal ions to chelate with the enzyme. 14 mL of NaOH (1 M) solution was added to the solution from step one, and the reaction was continued with stirring for another 2.5 h. The product was washed with deionized water, centrifuged, collected, and freeze-dried to obtain the bimetallic hydroxide functionalized bilayer mesoporous composite adsorbent (Zr-La-MHCS).

[0032] Figure 1 c and g are SEM and TEM images of the inoculum carbon spheres. As can be seen from the images, particulate matter is generated in both the inner and outer layers of the carbon spheres, and metal hydroxides grow uniformly on the surface of the carbon spheres, which proves that bimetallic hydroxides are generated in situ on the carbon spheres.

[0033] Example 2

[0034] Steps (1) and (3) are performed in the same way as steps (1) and (3) in Example 1.

[0035] (2) Preparation of enzyme-MHCS 30 mg of lysozyme (LYM) was added to 40 mL of deionized water to prepare a solution. 50 mg of MHCS nanoparticles prepared in step (1) were added to the enzyme solution, and LYM was immobilized on the MHCS nanoparticles through physical adsorption. The prepared solution was placed in a centrifuge tube and placed on a shaker for adsorption and fixation for 12 h. After centrifugation, the solution was washed with deionized water and freeze-dried for later use. Enzyme-MHCS was obtained.

[0036] Example 3

[0037] Steps (1) and (3) are performed in the same way as steps (1) and (3) in Example 1.

[0038] (2) Preparation of enzyme-MHCS 30 mg of lysozyme (LYM) was added to 40 mL of deionized water to prepare a solution. 50 mg of MHCS nanoparticles prepared in step (1) were added to the enzyme solution, and LYM was immobilized on the MHCS nanoparticles through physical adsorption. The prepared solution was placed in a centrifuge tube and placed on a shaker for adsorption and fixation for 12 h. After centrifugation, the solution was washed with deionized water and freeze-dried for later use. Enzyme-MHCS was obtained.

[0039] Example 4

[0040] Steps (1) and (2) are performed in the same manner as steps (1) and (2) in Example 1.

[0041] (3) Preparation of Zr-La-MHCS 25 mg of lanthanum chloride (LaCl3), 25 mg of zirconium oxychloride octahydrate (ZrOCl2·8H2O), and 30 mg of enzyme-inactivating carbon spheres prepared in step (2) were dispersed in 30 mL of HCl (0.1 M) solution. The mixture was stirred with a magnetic stirrer at room temperature for 2.5 h to allow the metal ions to chelate with the enzyme. 14 mL of NaOH (1 M) solution was added to the solution from step one, and the reaction was continued with stirring for another 2.5 h. The product was washed with deionized water, centrifuged, collected, and freeze-dried to obtain a bimetallic hydroxide functionalized bilayer mesoporous composite adsorbent (Zr-La-MHCS).

[0042] Example 5

[0043] Steps (1) and (2) are performed in the same manner as steps (1) and (2) in Example 1.

[0044] (3) Preparation of Zr-La-MHCS 30 mg of lanthanum chloride (LaCl3), 30 mg of zirconium oxychloride octahydrate (ZrOCl2·8H2O), and 30 mg of enzyme-inactivating carbon spheres prepared in step (2) were dispersed in 30 mL of HCl (0.1 M) solution. The mixture was stirred with a magnetic stirrer at room temperature for 2.5 h to allow the metal ions to chelate with the enzyme. 14 mL of NaOH (1 M) solution was added to the solution from step one, and the reaction was continued with stirring for another 2.5 h. The product was washed with deionized water, centrifuged, collected, and freeze-dried to obtain a bimetallic hydroxide functionalized bilayer mesoporous composite adsorbent (Zr-La-MHCS).

[0045] Example 6

[0046] Steps (1) and (2) are performed in the same manner as steps (1) and (2) in Example 1.

[0047] (3) Preparation of Zr-La-MHCS 50 mg of lanthanum chloride (LaCl3), 50 mg of zirconium oxychloride octahydrate (ZrOCl2·8H2O), and 20 mg of the enzyme-inactivating carbon spheres prepared in step (2) were dispersed in 30 mL of HCl (0.1 M) solution. The mixture was stirred magnetically at room temperature for 6 h to allow the metal ions to chelate with the enzyme. 14 mL of NaOH (1 M) solution was added to the solution from step one, and the reaction was continued with stirring for another 6 h. The product was washed with deionized water, centrifuged, collected, and freeze-dried to obtain the bimetallic hydroxide functionalized bilayer mesoporous composite adsorbent (Zr-La-MHCS).

[0048] Comparative Example

[0049] Preparation of monolayer S-Zr-La-MHCS: (1) Polymerization preparation of S-MHCS particles Tetrapropyl orthosilicate (TPOS, 3.46 mL), resorcinol (0.4 g), and formalin (37 wt%, 0.56 mL) were added to a solution consisting of ammonia solution (3.0 mL, 28 wt%), deionized water (10 mL), and ethanol (70 mL). The mixture was stirred vigorously at room temperature for 24 hours. The solid product was collected by centrifugation, dried overnight at 50 °C, carbonized under a N2 atmosphere at 70 °C, and the silica template was removed by etching with hydrofluoric acid (HF, 5%) to obtain S-MHCS.

[0050] Steps (2) and (3) are performed in the same way as steps (2) and (3) in Example 1, to obtain a single-layer S-Zr-La-MHCS.

[0051] The product Zr-La-MHCS obtained in Example 1 was subjected to performance testing:

[0052] like Figure 3 As shown, adsorption solutions with pH values ​​ranging from 2 to 8 were studied, and the corresponding zeta potential values ​​were measured. Different pH values ​​affect the zeta potential of the adsorbent surface and also influence the form in which fluoride ions exist. At higher zeta potentials, the material exhibits higher adsorption capacity for fluoride ions. However, at lower pH values, bound fluoride ions are predominantly in the form of HF, resulting in weaker electrostatic interactions and a decreased adsorption capacity. Nevertheless, high adsorption capacities are still observed at other pH values, indicating that the electrostatic interaction of the bimetallic hydroxide grown on the MHCS surface plays a major role in fluoride adsorption.

[0053] like Figure 4 As shown, the adsorption capacity of Zr-La-MHCS at different time points was investigated, and the data were fitted using pseudo-first-order and pseudo-second-order kinetic models, resulting in kinetic curves and their fitting curves. The adsorption process of Zr-La-MHCS can be divided into three steps. As can be seen from the figure, the adsorption rate of fluoride ions in the material is relatively fast. In the first 10 minutes, adsorption begins rapidly due to electrostatic interactions on the adsorbent surface, and the adsorption amount increases sharply. Between 10 and 30 minutes, the adsorption rate decreases, reaching equilibrium after approximately 50 minutes, where the adsorbent particles form a strong complex with the fluoride ions. The adsorption kinetics of different adsorbents under the same conditions were also compared. The adsorption equilibrium time of the comparative example S-Zr-La-MHCS was similar to that of Zr-La-MHCS, but its adsorption equilibrium capacity was lower, indicating that the bilayer matrix material has higher adsorption capacity. As can be seen from the figure, Zr-La-MHCS has a faster adsorption rate and a higher adsorption equilibrium capacity than commercial alumina adsorbents. In addition to comparative experiments with different adsorbents, the adsorption performance of Zr-La-MHCS adsorbent material with different volumes of fluorine solution was also investigated. The adsorption equilibrium capacity was lower when the volume of fluorine solution was 20 mL, indicating that the adsorption performance was better when the feed ratio was 2 mg: 9 mL.

[0054] Figure 5 The thermodynamic and adsorption model fitting curves were obtained at 288 K, 298 K, and 308 K, respectively. The adsorption capacity of Zr-La-MHCS increases with the increase of fluoride ion concentration, and the adsorption process is endothermic.

[0055] Figure 6 The effect of varying competing ion concentrations on fluoride removal via Zr-La-MHCS adsorption was demonstrated. The initial fluoride ion concentration was fixed at 20 mg / L in the experiment. -1Four interfering ions were prepared into mixed ion solutions at concentrations of 0, 1, 2, and 5 times that of fluoride ions, respectively. After adsorption at room temperature with 2 mg of adsorbent and 9 mL of the mixed ion solution for 3 h, the fluoride ion concentration was determined by ion chromatography, and the adsorption capacity was calculated. The decrease in fluoride ion adsorption capacity was minimal with changes in nitrate ion concentration, while changes in bicarbonate concentration had a greater impact on fluoride ion adsorption capacity. This may be because the hydrolysis of bicarbonate in water alters the pH, thus affecting the adsorption process.

[0056] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made using the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method for preparing a bimetallic hydroxide functionalized bilayer mesoporous composite adsorbent, characterized in that, Includes the following steps: (1) Preparation of double-layer mesoporous hollow carbon spheres (MHCS): Tetraethyl orthosilicate (TEOS), resorcinol, and formalin were added to a solution composed of ammonia solution, deionized water, and ethanol. The mixture was stirred vigorously at room temperature for t1, then TEOS was added and stirring continued for t2. Finally, the mixture was placed in a high-pressure autoclave lined with polytetrafluoroethylene for further hydrothermal treatment. The solid product was collected by centrifugation and dried overnight. After carbonization under N2 atmosphere and removal of the silica template by hydrofluoric acid etching, MHCS nanoparticles were obtained. (2) Preparation of enzyme-MHCS (enzyme carbon spheres): Lysozyme LYM was added to deionized water to prepare a lysozyme solution. The MHCS nanoparticles prepared in step (1) were added to the lysozyme solution. LYM was fixed on the MHCS nanoparticles by physical adsorption. The mixed solution was then placed in a centrifuge tube, placed on a shaker for adsorption and fixation, centrifuged, washed with deionized water, and freeze-dried for later use to obtain enzyme-MHCS carbon spheres. (3) Preparation of bimetallic hydroxide functionalized bilayer mesoporous composite adsorbent Zr-La-MHCS: Lanthanum chloride (LaCl3), zirconium oxychloride octahydrate (ZrOCl2·8H2O), and enzyme-MHCS carbon spheres were dispersed in HCl solution and stirred with a magnetic stirrer for a period of time to allow the metal ions to chelate with the enzyme. Then, NaOH solution was added, and the reaction was continued with stirring. After centrifugation, the mixture was washed with deionized water and freeze-dried to obtain the bimetallic hydroxide functionalized bilayer mesoporous composite adsorbent Zr-La-MHCS.

2. The preparation method according to claim 1, characterized in that, In step (1), the ratio of the initially added tetraethyl orthosilicate (TEOS), resorcinol, formalin, ammonia solution, deionized water, ethanol, and subsequently added TEOS is 2.8 mL: 0.4 g: 0.56 mL: 3.0 mL: 10 mL: 70 mL: 1.5 mL; wherein the concentration of formalin is 37 wt% and the concentration of ammonia solution is 28 wt%. The stirring time t1 is 6 hours, and the stirring time t2 is 24 hours; The hydrothermal treatment was carried out at a temperature of 100℃ for 24 hours. The carbonization temperature is 700℃, and the concentration of hydrofluoric acid is 5%.

3. The preparation method according to claim 1, characterized in that, In step (2), the ratio of lysozyme LYM to deionized water is 30-60 mg: 30-50 mL; the mass-volume ratio of MHCS to lysozyme aqueous solution is 30-60 mg: 30-50 mL.

4. The preparation method according to claim 3, characterized in that, In step (2), the ratio of LYM to deionized water is 30 mg: 40 mL; the mass-volume ratio of MHCS and lysozyme aqueous solution is 20.0 mg: 40 mL.

5. The preparation method according to claim 1, characterized in that, In step (2), the adsorption fixation time is 12.0 h.

6. The preparation method according to claim 1, characterized in that, In step (3), the mass-volume ratio of LaCl3, ZrOCl2·8H2O, enzyme-MHCS and HCl solution is 20-50 mg: 20-50 mg: 20-50 mg: 20-50 mL.

7. The preparation method according to claim 6, characterized in that, In step (3), the mass-volume ratio of LaCl3, ZrOCl2·8H2O, enzyme-MHCS and HCl solution is 25 mg: 25 mg: 50 mg: 30 mL, wherein the concentration of HCl solution is 0.1 M.

8. The preparation method according to claim 1, characterized in that, In step (3), the volume ratio of NaOH solution to HCl solution is 10~20 mL: 20~50 mL, and the concentration of NaOH solution is 1M.

9. The preparation method according to claim 1, characterized in that, In step (3), the stirring reaction time is 2.5 h, and the condition is room temperature.

10. The use of the bimetallic hydroxide functionalized bilayer mesoporous composite adsorbent Zr-La-MHCS prepared by the preparation method according to any one of claims 1 to 9 for the adsorption and separation of fluoride ions.

Citation Information

Patent Citations

  • Bio-adsorbent prepared by modifying ball-milled tea residues and preparation method and application of bio-adsorbent

    CN105688865A

  • Magnetic nano adsorbent for adsorbing mercury ions and preparation and application thereof

    CN110142031A